A sign of her own - Marsh, Sarah (Novelist) (Park Row Books, 2024)
Ellen Lark is on the verge of marriage when she and her fiancé receive an unexpected visit from Alexander Graham Bell. Ellen is deaf and for a time she was Bell's student learning visible speech. During their lessons, Bell also confided in her about his dream of producing a device that would transmit the human voice along a wire: the telephone. Now, on the cusp of wealth and renown, Bell wants Ellen to speak up in support of his claim to the patent of the telephone, which is being challenged by rival inventors. But Ellen has a different story to tell: that of how Bell betrayed her and other deaf pupils in pursuit of his own ambition. Ellen knows that this is her one opportunity to tell the true story--her story--but to do so will risk her engagement, her future prospects and her mother's last wish for her.